MicroRNA Protocols - Shao- Yao-Ying [ Editor ] (Methods in molecular biology , v. 342., 2006)
MicroRNA Protocols provides diverse, novel, and useful descriptions of miRNAs in several species, including plants, worms, flies, fish, chicks, mice, and humans. These include some useful adaptations and applications that could be relevant to the wider research community who are already familiar with the identification of miRNAs. This volume will stimulate the reader to explore diverse ways to understanding the mechanism in which miRNAs facilitate the molecular aspects of the biomedical research.